Distribution of humpback whales along the coast of Ecuador and management implications - Felix , Fernando; Haase, Ben (J. Cetacean Res. Manage., 2023)
As part of a long-term population study of humpback whales breeding on the coast of Ecuador (2°S, 81°W), four sites on the central coast were surveyed: Puerto Cayo, Puerto López, La Plata Island and Salinas. The spatial, temporal and age class distributions of 322 groups positioned during the period of 1996-2003 were analysed regarding their distance from the shore and water depth with two statistical methods: one-way ANOVA and linear modelling. The average sighting distance from shore varied between 5.31km in Salinas and 10.16km in Puerto Cayo with mid values in Puerto López and La Plata Island. Average water depth was similar in Puerto López, La Plata Island and Salinas (36-39m) but lower in Puerto Cayo (19.43m). Differences were highly significant in both cases (p<0.01). A progressive but not significant increase in the average distance from shore was found (6.2km in June to 7.17km in September). Sighting depth was constant between June and August (average 35-36m) but decreased significantly in September to 27m (p<0.01). This difference was attributed to the presence of mother-calf pairs in shallower water by the end of the season. Age class analyses using ANOVA showed highly significant differences between groups of adults, and adults with subadults with respect to singleton subadults, and groups containing a mother-calf pair for both distance from shore and depth (p<0.01); however, linear modelling analyses showed only depth was significant (p=0.026). This suggests that depth is a more important determinant of differences in distribution between these age classes than proximity to shore. The sightings distribution showed segregation of both mother-calf pairs (towards shallow waters) and of singleton subadults (towards the boundaries of the surveyed area). Since only eight sightings (2.5%) were in waters deeper than 60m, we propose that depth is a major feature determining humpback whale distribution in these waters. Implications of this coastal distribution are discussed, particularly with respect to bycatch in fishing gear and whalewatching. A review of recent southeast Pacific sightings showed that humpback whales are also abundant in coastal waters to the southwest of Ecuador (3°S) and confirmed that they are scarce offshore. However, whales are more widely distributed in the north of Peru (4°-6°S) where they make the transition between deeper oceanic and shallower coastal waters when arriving at and leaving the breeding area.